Optimal Income Taxation, Public-Goods Provision and Public-Sector Pricing : A Contribution to the Foundations of Public Economics - Martin Hellwig (Max Planck Institute for Research on Collective Goods, 2004)
The paper develops an integrated model of optimal nonlinear income taxation, public-goods provision and pricing in a large economy. With asymmetric information about labour productivities and publicgoods preferences, the multidimensional mechanism design problem becomes tractable by requiring renegotiation proofness of the final allocation of private goods and admission tickets for excludable public goods. Under an affiliation assumption on the underlying distribution, optimal income taxation, public-goods provision and admission fees have the same qualitative properties as in unidimensional models. These properties are obtained for utilitarian welfare maximization and for a Ramsey-Boiteux formulation with interim participation constraints.
Keywords: D82; H20; H40; 330; Optimal Income Taxation; Public Goods; Public-Sector Pricing; Multidimensional Mechanism Design; Ramsey-Boiteux Pricing; Optimale Besteuerung; Öffentliches Gut; Ramsey-Preis; Gebühr; Wohlfahrtseffekt; Theorie